The Exhaustion of the Administrative Way in Modern Administrative Law. - Rojas Ortega, Alex (2021)
In 2006, the Constitutional Court declared the completion of the administrative procedure as optional, except for two specific areas: municipal and public procurement. However, to this date, under current administrative law, completion of the administrative procedure must be understood as optional, always, in all scenarios, without any distinction, in protection of an individual's subjective interests.